Annual Plan 2004-05 Government of Punjab - Planning Commission (Planning Commission, 2004)
The size of the 9th Five Year Plan (1997-02) was approved at Rs. 11500 crore at 1993-94 constant prices by the Planning Commission, (Rs. 14300 Crore at current prices), against an outlay of Rs. 6570 Crore for the 8th Plan. Against the final outlay of Rs. 12753 Crore (sum of Annual plan outlays) of 9th Five Year Plan, an expenditure of Rs. 10028.53 Crore was incurred by the end of 9th Plan indicating financial performance of 80%. The shortfall in expenditure is mainly attributed to constraints ~n State’s financial resources on account of implementation of the 5th Pay Commission report, substantial increase in the NonPlan expenditure and non-release of State share under the centrally funded projects/ schemes by the Govt, of India and other financial institutions.
Government of Punjab Department of Planning